A Protoype System for Transmitting Power through Radio Frequency Signal for Powering Handheld Devices - Olakanmi O.Oladayo (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Miniature devices development has been greatly complementing the technology developmental trend in telecommunication. This makes the new communication technology to sail smoothly into the society and creating unexpected market for both the telecommunication providers and embedded system manufactures. However power has been the major problem in the usage of some of these devices most especially in third world countries where power is epileptically supplied. This paper proposes a prototype system which wirelessly generates DC for charging and powering power-critical handheld and remotely located devices. The design captures 900MHz radio frequency signal with a dipole antenna, which is converted into DC and stores the power in the device’s battery or use it to power it. The major aim of this paper is to provide a prototypical system which provides a cheap, constant and environmental friendly system for powering and charging power critical handheld and remote devices thereby prevents systems failure due to power loss.DOI:http://dx.doi.org/10.11591/ijece.v2i4.572